KEPEMIMPINAN DALAM PENGAMBILAN KEPUTUSAN - Bhudianto, Wahyu (Transformasi, 2015)
The leadership role is a set of expected behavior, carried out by people in accordance with itsposition as a leader. The role of the leader is very large in making decisions and takingresponsibility for the outcome. The decision reflects the character of a leader. Decision-making iscentral to the organization's activities are also a key leadership or the core of leadership.Leaders must be able to take decisions in a variety of situations, by choosing the best among anumber of alternative alternatis decisions it faces. Alternatidf should be chosen that its smallestnegative risk so as not to harm the organization. Leaders must be able to explain the reason - thereason for choosing one alternative decisions in a way that is most easily understood in order toget support in implementationKey words: leadership, decision-making